Seroprevalence of SARS-CoV-2 significantly varies with age: Preliminary results from a mass population screening. Issue 6 (December 2020) - Pagani, Gabriele; Conti, Federico; Giacomelli, Andrea; Bernacchia, Dario; Rondanin, Rossana; Prina, Andrea; Scolari, Vittore; Gandolfi, Cecilia Eugenia; Castaldi, Silvana; Marano, Giuseppe; Ottomano, Cosimo; Boracchi, Patrizia; et al.
Graphical abstract: Image, graphical abstract